2021
DOI: 10.1080/07388551.2021.1947183
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of Yarrowia lipolytica for terpenoids production: advances and perspectives

Abstract: Terpenoids are a large family of natural products with diversified structures and functions that are widely used in the food, pharmaceutical, cosmetic, and agricultural fields. However, the traditional methods of terpenoids production such as plant extraction and chemical synthesis are inefficient due to the complex processes, high energy consumption, and low yields. With progress in metabolic engineering and synthetic biology, microbial cell factories provide an interesting alternative for the sustainable pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 110 publications
0
34
0
Order By: Relevance
“…As the cultivation time goes by, the concentration of extracellular β-caryophyllene gradually decreases due to the volatility of β-caryophyllene. Only 5% of β-caryophyllene was detected in the extracellular after 42 h. Although most of the sesquiterpenoids are not suitable for intracellular accumulation due to their characteristics, such as cytotoxicity, evaporability, or secretion [ 38 ], our research showed that the β-caryophyllene primarily accumulated in the intracellular.
Fig.
…”
Section: Resultsmentioning
confidence: 76%
“…As the cultivation time goes by, the concentration of extracellular β-caryophyllene gradually decreases due to the volatility of β-caryophyllene. Only 5% of β-caryophyllene was detected in the extracellular after 42 h. Although most of the sesquiterpenoids are not suitable for intracellular accumulation due to their characteristics, such as cytotoxicity, evaporability, or secretion [ 38 ], our research showed that the β-caryophyllene primarily accumulated in the intracellular.
Fig.
…”
Section: Resultsmentioning
confidence: 76%
“…As an oleaginous yeast, Y. lipolytica possesses an active tricarboxylic acid cycle and a pentose phosphate pathway, which supports high fluxes of acetyl‐CoA, NADPH, and the ATP supply by metabolizing a variety of carbon sources (Muhammad et al, 2020; Zhang et al, 2022). The characteristic gives it great potential for the production of terpenoids and lipids.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several groups developed various host cells, advanced strategies, and tools for the microbial production of terpenoids ( Carsanba et al, 2021 ; Zhang et al, 2021 ; Rinaldi et al, 2022 ). However, as shown in Table 3 , only a few studies explored the biorefining of various forms of organic waste to produce terpenoid flavor and fragrance compounds ( Table 3 ; Yao et al, 2020 ; Zhuang et al, 2020 ; Styles et al, 2021 ; Szotkowski et al, 2021 ; Wei et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Y. lipolytica is a GRAS yeast that, due to its endogenous mevalonate pathway (MVA), high capacity to generate acetyl coenzyme A, efficient lipid metabolism, and wide substrate scope, is rapidly emerging as a promising tool for the production of terpenoids ( Ma et al, 2019 ; Li et al, 2021 ; Zhang et al, 2021 ). Metabolic engineering strategies and synthetic biology tools raise the possibility of redirecting microbial carbon fluxes in Y. lipolytica to create efficient cellular pathways for the production of natural compounds ( Schwartz et al, 2016 ; Liu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%